(untitled) (Academic Journal of Internal Affairs, 2024)
Aim: One of the biggest challenges people face today is the development of an effective and efficient defence capability against cyber attacks. Nowadays, this is not only an expectation at the public level, but also a real need at the corporate and private user level. In this study, the author primarily wishes to draw attention to the global trends of new types of threats in the 21st century, the most vulnerable sectors, as well as to the development possibilities of the cyber security capabilities of domestic hazardous plants. Methodology: The author has conducted a qualitative research method using primary and secondary data to identify current trends and attack vectors of threats in cyberspace at global and regional levels. In addition, the author has also conducted empirical research using primary data to determine the development possibilities of the management/safety management systems of plants dealing with hazardous substances, as well as to build the resilience of the electronic information systems of these plants against cyber threats. Findings: The number of cyber-attacks have continued to grow over the last few decades, and industrial companies have become the main targets of these new types of attacks. In order for Hungary to develop an effective defence capability, especially in the case of industrial actors, it is important to create the cyber defence capability of plants dealing with hazardous materials under the supervision of the disaster management, industrial safety authority. Value: Taking stock of the possibilities of developing the security management system of domestic hazardous materials plants to protect against 21st century threats. This scientific work intends to provide more detailed information on the addition and feasibility of the management system with information security aspects.